A change management case study using Appreciative Intelligence®. (1st January 2013) - Lemons, R. Mikel; Thatchenkery, Tojo
This study explored how Appreciative Intelligence-based approaches and Appreciative Inquiry principles could address resistance to change in an educational institution. Results showed that personal communication meetings and knowledge sharing were critical during leadership transition. To reframe resistance to change as a constructive quality, four core values or Life Giving Forces (LGFs) of the organisation were identified. An elaborate Appreciative Inquiry-based organisational analysis was conducted building on the core values which led to the generating of several 'future-present scenarios' for implementation. The power of the unconditional positive questions in communication meetings to create a positive organisational climate was demonstrated in this case study. As a pre-test revealed a resistance to change among the participants, Appreciative communication programmes were designed and implemented to address it. Post-tests indicated that the effort was successful in helping others 'see the mighty oak in the acorn'. The key learning from this study was that higher education leaders should proactively create a readiness for change in the faculty, staff, and administration prior to making radical changes by leveraging the positive energy that exist in the institution. This was best accomplished by reframing resistance to change as an opportunity and redefining personal communication meetings as a tool for knowledge sharing and for creating a positive organisational climate.